2008
DOI: 10.1007/s10735-008-9171-4
|View full text |Cite
|
Sign up to set email alerts
|

Developmental patterns of caspase-3, bax and bcl-2 proteins expression in the human spinal ganglia

Abstract: The distribution of the bcl-2, bax and caspase-3 proteins was investigated in the cells of developing human spinal ganglia. Paraffin sections of 10 human conceptuses between 5th and 9th gestational weeks were analysed morphologically, immunohistochemically and by TUNEL-method. Cells positive to caspase-3 had brown stained nuclei or nuclear fragmentations. At earliest stages, 6% of ganglion population were caspase-3 positive cells. Later on, a significant increase in number of caspase-3 positive cells appeared,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…To identify the onset of differentiation of the neuronal subtypes that express NF200, IB4, CGRP, calretinin, and VR1 during early human development, we immunohistochemically analyzed localization, proportion, and expression intensity of those markers in human spinal ganglion cells between the fifth week and tenth week of development. During the initial differentiation of neural crest cells, the SG cells exhibited the first sign of differentiation toward neurons by nestin positivity, as shown in our previous studies (Vukojevic et al, ; Vukojevic et al, ) and the commencement of expression of some neuronal subtype markers.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…To identify the onset of differentiation of the neuronal subtypes that express NF200, IB4, CGRP, calretinin, and VR1 during early human development, we immunohistochemically analyzed localization, proportion, and expression intensity of those markers in human spinal ganglion cells between the fifth week and tenth week of development. During the initial differentiation of neural crest cells, the SG cells exhibited the first sign of differentiation toward neurons by nestin positivity, as shown in our previous studies (Vukojevic et al, ; Vukojevic et al, ) and the commencement of expression of some neuronal subtype markers.…”
Section: Discussionsupporting
confidence: 81%
“…Many studies over the past years have revealed a number of factors that are involved in the development of the SG neurons (Jungnickel et al, 2005;Strelau et al, 2009;Vukojevic et al, 2008Vukojevic et al, , 2009Vukojevic et al, , 2010. Although many of these factors have been identified, some important questions about the differentiation of the human SG neurons remained unsolved.…”
Section: Introductionmentioning
confidence: 99%
“…The standard haematoxylin-eosin staining method for the vessel wall tissue and the Sulphated Alcian Blue method for the demonstration of intracellular or extracellular localization of mast cell granules were used. Immunofluorescent methods were performed to show fibrinogen-fibrin and IgG deposits in the endarterectomy specimens as described previously [19]. The number of mast cells and mononuclear cells were counted in 20 random high power fields (× 400).…”
Section: Methodsmentioning
confidence: 99%
“…To examine the relationship between Bcl-2 and Bax expression in the same cell (rabbit anti-mouse 1:600; Chemicon ® International, Inc.) double immunofluorescence staining with appropriate secondary antibodies (T-862, Jackson Immuno Research Lab., PA, USA, sc-2090, Santa Cruz Biotechnology, Inc., Santa Cruz, CA, USA and Texas Red, sc-2780, Santa Cruz Biotechnology, Inc., Santa Cruz, CA, USA) was used as we described previously (Vukojevic et al, 2008). To examine the DNA fragmentation in apoptotic cells, the TUNEL method (Fluorescein FragEL DNA Fragmentation Detection Kit, Calbiochem, USA) was combined with sheep anti human/mouse/rat AIF (1:500; AF5824, R&D Systems, Minneapolis, USA) staining.…”
Section: Double Immunofluorescence Staining With Bcl-2 and Bax Antibomentioning
confidence: 99%
“…Apoptosis is energy dependent form of cell death which requires activation of specific sets of genes and enzymes, including cysteine aspartylspecific proteases (caspases), intracellular enzymes involved in the final steps of the limb apoptosis (Zuzarte-Luis and Hurle, 2002). By now, caspase-3 dependant cell death has been found in different organs such as thymus, small intestine, kidney and neurons of mice, as well as in the spinal ganglia and other human organs (Krajewska et al, 1997;Raff et al, 1993;Vukojevic et al, 2008). To date, role of caspase-3 mediated cell death has been analyzed during limb development in mice (Ali-Khan and Hales, 2003) and chickens (Montero and Hurle, 2010) but not in humans.…”
Section: Introductionmentioning
confidence: 99%